Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/acssuschemeng.9b02672
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Evolution Reaction (OER) on Clean and Oxygen Deficient Low-Index SrTiO3 Surfaces: A Theoretical Systematic Study

Abstract: SrTiO3 (STO) is a widely used photocatalyst for water splitting, which has no photoactivity without a cocatalyst. The reason for this unclear. Here, we performed an oxygen evolution reaction (OER) on clean and oxygen deficient (100), (110), and (111) surfaces on STO by density functional theory. Combining our results with experimental results in the literature, we demonstrated that the overpotential is small enough for OER to occur on (100) surfaces. There is no photoactivity due to the photogenerated holes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…According to recent developments, the photogenerated charge is shared between different facets of a semiconductor crystals with low symmetry [19,20]. Among other materials for water splitting, strontium titanate SrTiO 3 (STO) is well known [15,18,[21][22][23][24][25][26][27][28][29][30], where the processes of water adsorption and dissociation have been studied in detail [31][32][33]. Despite the fact that many semiconductor crystals are highly symmetric and have isotropic facets that are not suitable for charge separation between faces, it was found that the selective distribution on the anisotropic faces of 18-facet strontium titanate nanocrystals leads to a noticeable increase of apparent quantum efficiency [9].…”
Section: Introductionmentioning
confidence: 99%
“…According to recent developments, the photogenerated charge is shared between different facets of a semiconductor crystals with low symmetry [19,20]. Among other materials for water splitting, strontium titanate SrTiO 3 (STO) is well known [15,18,[21][22][23][24][25][26][27][28][29][30], where the processes of water adsorption and dissociation have been studied in detail [31][32][33]. Despite the fact that many semiconductor crystals are highly symmetric and have isotropic facets that are not suitable for charge separation between faces, it was found that the selective distribution on the anisotropic faces of 18-facet strontium titanate nanocrystals leads to a noticeable increase of apparent quantum efficiency [9].…”
Section: Introductionmentioning
confidence: 99%
“…It also shows outstanding chemical stability but its OER-related electrocatalytic activity is rather low, in part also due to its wide bandgap. 38,39 As in the case of TiO 2 , Rh and V were used as the p-type and n-type dopant, respectively. The results of the thermodynamic analysis of the OER catalysis on pristine and doped SrTiO3 structures are summarized in Fig.…”
Section: Coulombic Effectmentioning
confidence: 99%
“…The HOO * adsorbate also had two configurations: one where hydrogen bonded to surface oxygen (Figure 5d), denoted as H (O surf ) OO * , and the other where hydrogen bonded to the adsorbate's oxygen (Figure 5e), denoted as HOO * . In [14], only the second configuration was mentioned, although its adsorption energy was significantly higher than that of the H (O surf ) OO * configuration: 4.24 eV versus 3.64 eV.…”
Section: Oxygen Evolution Reaction (Oer) Intermediatesmentioning
confidence: 99%
“…Strontium titanate SrTiO 3 (STO) is a well-known material for water splitting [1][2][3][4][5][6][7][8][9][10][11][12]. The process of water adsorption and dissociation was studied in detail [13][14][15]. The effects of doping are investigated in [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation